Performance of publish - Farooq, Umar (Software engineering notes.)
Publish/subscribe middlewares are becoming popular for distributed applications because of their flexible and scalable nature. Anonymous and loosely-coupled communication between publisher and subscriber, along with the inherently asynchronous nature of these systems, help them adapt quickly to changing environments, making them a good choice for mobile cellular networks. This paper studies publish/subscribe middleware performance in such networks in detail. As a first step, the paper characterizes a popular implementation of publish/subscribe system for the mobile domain, studying and analyzing the effect of different mobility parameters, which to the best of our knowledge is the first experimental research on the performance behavior of publish/subscribe systems in a mobile wireless domain. As a second step the paper presents the design, implementation and evaluation of middleware level handoffs, a well known solution to extend publish/subscribe systems to a mobile domain, and identifies the performance concerns of such extensions. The results show that such handoff protocols involving two brokers are impractical from a performance perspective under highly dynamic and unreliable mobile wireless settings. The paper identifies the basic reason for the limitations of middleware level handoffs.